Preparation and recovery of iron carbide from pyrite cinder using carburization-magnetic separation technology - Chen D.; Gou H.; Lv Y.; Li P.; Yan B.; Xu J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A new technique with carburization followed by magnetic separation is presented for the preparation of high-grade iron carbide from pyrite cinder to promote the high value-added utilization of pyrite cinder. The effects of carburizing temperature, carburizing time and Na2SO4 dosage on carburized pellets were investigated, and the effects of Na2SO4 dosage and grinding fineness on magnetic concentrate were carried out. The optimized process parameters were proposed as follows: carburizing at 650°C for 180 minutes in CO-CO2-H2 gas mixtures, Na2SO4 dosage of 9%, magnetic field intensity of 130 mT, and grinding fineness of 92.25% powder passing 0.025mm. The iron content, total carbon content, total iron and carbon content of magnetic concentrate were 82.62%, 5.60%, and 88.22%, respectively. The recovery rate of iron reached 88.67%. The behaviors and mechanisms of carburization, separation, and Na2SO4, were ascertained with optical microscopy, X-ray powder diffraction (XRD), and scanning electron microscope (SEM).